2017
DOI: 10.1002/mrm.26834
|View full text |Cite
|
Sign up to set email alerts
|

Variability of 4D flow parameters when subjected to changes in MRI acquisition parameters using a realistic thoracic aortic phantom

Abstract: Peak flow, mean velocity, and stroke volume from 4D flow data are more sensitive to changes of temporal than spatial resolution, as opposed to wall shear stress, which is more sensitive to changes in spatial resolution. Magn Reson Med 79:1882-1892, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…It is well-known that the spatial resolution of MRV is not sufficient to accurately determine the wall shear stress directly from the near-wall velocity gradient. However, it is in general not assumed that a low temporal resolution can reduce the wall shear stress estimation in the same order as the spatial resolution does (Montalba et al 2018;Zimmermann et al 2018). With the use of the temporally highresolved LDV and CFD data of this work, it was shown that the underprediction may indeed be very large.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that the spatial resolution of MRV is not sufficient to accurately determine the wall shear stress directly from the near-wall velocity gradient. However, it is in general not assumed that a low temporal resolution can reduce the wall shear stress estimation in the same order as the spatial resolution does (Montalba et al 2018;Zimmermann et al 2018). With the use of the temporally highresolved LDV and CFD data of this work, it was shown that the underprediction may indeed be very large.…”
Section: Resultsmentioning
confidence: 99%
“…The hose was connected to a MRI-compatible flow pump (CardioFlow 5000 MR, Shelley Medical Imaging Technologies, London, ON, Canada) with a constant flow rate of 200 mL/s. The system was filled with a blood-mimicking fluid (40% distilled H2O, 60% Glycerol) and the set up was similar as in [12], [13]. The MRI data sets were acquired on a clinical 1.5T Philips Achieva scanner (Philips, Best, The Netherlands).…”
Section: B Phantom Datamentioning
confidence: 99%
“…However, 2DRF pulse durations of about 3.5 ms reduced the temporal resolution compared with conventional 1‐dimensional (1D) slab‐selective RF pulses (1DRF, such as SINC) . The temporal resolution is, however, critical for correct peak flow quantification . Furthermore, the reduced FOV (rFOV) needs to be oversampled in both phase‐encoding directions (i.e., rFOV > FOX), to prevent static spatial aliasing, which prolongs the scan time.…”
Section: Introductionmentioning
confidence: 99%
“…15 The temporal resolution is, however, critical for correct peak flow quantification. [16][17][18] Furthermore, the reduced FOV (rFOV) needs to be oversampled in both phase-encoding directions 19 (i.e., rFOV > FOX), to prevent static spatial aliasing, 19 which prolongs the scan time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation